KEKERASAN DALAM RUMAH TANGGA DARI PERSPEKTIF HAK ASASI MANUSIA - A.Reni Widyastuti (Masalah-Masalah Hukum, 2011)
All kinds of violence, especially domestic violence, be human rights infringement and crime towards humanity dignity with discrimination form that must be wiped off. Domestic violence often accepted by woman as victim and at the time of same actually they have overrided rights and their autonomy is as individual by family wholeness and children future. So protection towards victim from violence in household be our responsibility with, as individual, society, law enforcer and government.